A função social como máscara do direito absoluto de propriedade rural no ordenamento jurídico brasileiro: uma análise crítica do legislador constituinte de 1987 e da função social no texto constitucional - Meneses, Danuza Farias Dantas (2021)
The present work is a bibliographical and documentary research that analyses the interpretation and applicability of the social function of the rural property in the Brazilian legal system from the perspective of the Symbolic Constitutionalization Theory, from the Constituent Assembly, 1987, to the current scenario in Brazil. The aim is to understand, therefore, if there is an absence of normative-legal implementation of the principle of the the social function of rural property due to the overlapping of the political system with the legal system; the principle object of this work having a merely symbolic function as a consequence of its constitutionalization. For this, it goes deeper into issues concerning the origin of private property, the accumulation of wealth, class society, the State, and the observation of social inequalities generated from the development of a new mode of production of wealth and society. The Liberal State model and the inequalities arising from it put in tension the strictly liberal economic and political model, which gave rise to the discussion of attributing a social function to property as a political concession for maintaining the status quo; conditioning it not only to an economic character, but also to a social one. Then, the observations about the functionalization of property in the face of this new State model are deepened, pointing out the first problematizations - benefits and limitations - about the discussions about the constitutionalization of the social function as a conditioning mechanism of the right to property. It can be seen, from the above-mentioned notes, that the social function of rural property as a constitutional principle used as a mechanism for democratizing access to land and for carrying out agrarian reform, has not been able to substantially reduce the high rate of land concentration Brazilian. Therefore, the general objective to be achieved by the present work is to verify whether the right to private property overlaps the principle of the social function of rural property and its regulation in the Brazilian legal system due to the overlap of the political system to the legal system, making it impossible to normative-legal implementation of the Federal Constitution of 1988 - which should function as an intersystemic structural coupling, regulating their interpenetrations - and, consequently, enabling the normative-legal implementation of the constitutional rule. In this way, the dissertation in question intends to prove the hypothesis that the principle of the social function of the rural property fulfills a merely symbolic character in its negative aspect, working both as an alibi-legislation and a mechanism to postpone the solution of social conflicts through commitments dilatory, making it impossible to implement the Agrarian Reform, serving as a protection/shielding mechanism for rural private property, ratifying, in practice, the absolute right to property.